The Balanced Scorecard Concept as a Measurement of Sharia Cooperative Performance Through SWOT Analysis - Suryana,; Laksono, R. Roosaleh; Yusuf, Paulus Sugianto (Technium Business and Management, 2025)
A cooperative is a group of people who joined freely to meet their common economic, social, and cultural needs and aspirations through a business that is jointly owned and democratically managed, Meanwhile, sharia cooperatives are cooperatives that carry out their activities in a halal and good manner and integrate Islamic economic principles, such as the prohibition of usury, gharar, no speculation, and encouraging social awareness in every activity. This research is a qualitative research with a descriptive analysis method with a multi-case study on mosque-based sharia cooperatives in Bandung City, Indonesia. Mosque-based sharia cooperatives are sharia cooperatives established by mosque administrators with the aim of improving the welfare of mosque congregations in particular and the community around the mosque in general, also as an effort to reduce the community's dependence on loan sharks, save the community's faith from the dangers of usury, increase Islamic brotherhood through empowering the community's economy, increase the welfare of members and help develop micro, small and medium enterprises (MSMEs), and can alleviate poverty, but in reality, sharia cooperatives are not developing, the level of profitability is low and tends to continue to decline, the number of members does not increase and even tends to decline, the potential for prospective members is low and tends not to be interested in becoming cooperative members. Loan sharks are rampant and the poverty rate tends to decline. The results of this study indicate that performance measurement in existing Islamic cooperatives is only measured from a financial perspective and not from a non-financial perspective. The solution is that mosque-based sharia cooperatives must implement the Balance Scorecard (BSC) concept to measure the performance of sharia cooperatives in more detail, both from the financial and non-financial sides